(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Moringa oleifera (drumstick plant) is one of the most popular plants, which is believed to have enormous health benefits. Because of its health benefits, the demand of this plant is increasing day by day in different parts of the Indian subcontinent. Moringa leaves are used as a vegetable item in some parts of Bangladesh. In this study, we investigated the anti-hemolytic and anti-oxidative effects of hot water extract of M. oleifera leaves. The extract contained considerable amounts of different antioxidants: ????-carotene (87.50±12.00 g/g of extract), and phytochemicals such as total polyphenols (53.52±1.10 mg Gallic acid equivalent/g of extract) and flavonoids (10.40±1.40 mg catechin equivalent/g of extract). The antioxidant potential of the extract was assessed by its DPPH (2, 2-diphenyl-1-picrylhydrazyl-)-free radical scavenging activity, with M. oleifera leaf extract showing considerable anti-oxidative potentials. To evaluate the anti-hemolytic effect of the extract, freshly prepared erythrocytes were incubated with Fenton’s reagents in the absence or presence of the extract. We observed that erythrocytes pretreated with the extract exhibited a reduced degree of in vitro hemolysis. To support the anti-oxidative properties, tissues were treated with or without extract in the presence of Fenton’s reagents, and the levels of lipid peroxide (LPO) were determined. The Moringa oleifera leaf extract significantly decreased the levels of LPO in brain, liver and heart tissues. Our studies suggest that the Moringa oleifera leaf extract can mediate, at least partially, cytoprotective effects through scavenging of free radical, reduction of intracellular oxidative stress, and hence prevented the in vitro hemolysis of erythrocytes.